(untitled) (Historia, 2021)
For the most part, the inter-war years in South Africa have been researched as the time when African nationalism and resistance developed. Many such studies analyse the work of African intellectuals (mostly men) in this period while the role of women has become a serious consideration since the 1980s. In her book, A World of their Own: A History of South African Women’s Education (2013), Meghan Healy-Clancy examines the role of education for black women from the 1800s as a way to study their experiences in the late nineteenth and early twentieth centuries. Her book raises questions about the less public nature of black women’s lives, such as family, marriage and education. This paper aims to enter this conversation by examining the mobility of black women through a selection of articles which appeared in The Bantu World during 1935. Mobility is understood as an intensely political expression of movement which is also part of the quotidian. The analysis of these articles argues for a more complex understanding of the lives of black women, one beyond the narrative of subjugated women who did not have access to mobility, freedom and agency.